1956
DOI: 10.1071/bi9560130
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Temperature on the Level of Plasma Antidiuhetic Substances in the Rat

Abstract: 'rhe level of plasma antidiuretic substances (ADI:-i) was found to be doubled when rats were exposed continuously to an atmosphere of !l5�F (:35�C) and :30 mm Hg water vapour pressure for 28 days, and it, was reduccd to half with continuous exposure to cold (43�F (G�5�e)). When recluction in body woight accompanited IlEmting, the antidiuretie potency of tho blood was markedly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
1980
1980

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…1967) and thereby reduce salivary evaporation. Increased secretion of ADH has been observed in rats during heat stress (Itoh 1954;Robinson and Macfarlane 1956).…”
Section: Discussionmentioning
confidence: 97%
“…1967) and thereby reduce salivary evaporation. Increased secretion of ADH has been observed in rats during heat stress (Itoh 1954;Robinson and Macfarlane 1956).…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently several attempts have been made to increase the sensitivity of rats to exogenous ADH so that physiological concentrations of the hormone could be measured in plasma (e.g. Dicker, 1953;Robinson & MacFarlane, 1956; Dettelbach, 1958) but in general, such modifications have not been successful. Nevertheless, there are several reports of rats, prepared in the manner of Jeffers et al (1942), which showed significant responses to small doses of ADH (Gupta, Chaudhury & Chhuttani, 1967;Forsling, Jones & Lee, 1968).…”
Section: Introductionmentioning
confidence: 99%